Emergence of brand extension opportunities for SMEs products and services through hypermarket corporate brand - Hasliza Hassan, Hassan; Rahman, Muhammad Sabbir; Abu Bakar , Sade; Wan Mohd Nazdrol Wan Mohd , Nasir (2015)
The availability of hypermarket corporate brand extension products has given those consumers who are living on a tight budget and those who are price conscious the chance to purchase basic household necessities at affordable prices. Accordingly, the enhancement of self-service shopping experience through additional service facilities and sub-retailers has encouraged more consumers to shop at a particular hypermarket outlet. A hypermarket corporate brand extension that is offered through strong collaboration with small and medium enterprises (SMEs) provides more opportunities for the hypermarket to be competitive, and, at the same time, share the benefits with the SMEs. This research looks at the opportunities for SMEs to market their products and services through the corporate retail brand of hypermarkets within Malaysia. The findings for this research were made based on general observation as well as through support from other findings by various research scholars within this field. Presently, there are ample opportunities for SMEs to be involved in the retailing industry by becoming a business partner to supply products through hypermarket corporate brand extension strategies. The hypermarket retailers are also able to create an alliance with SMEs by outsourcing the enhancement and maintenance of the service facilities. The findings based on this research are expected to streamline the existing knowledge in this field through further empirical research. Keywords: Brand, Corporate, Enterprise, Extension, Hypermarket, Product, Service